SELF- CENSORSHIP BY PAKISTANI JOURNALISTS: CAUSES AND EFFECTS - Ghauri, Dr.Muhammad Junaid (Journal of Peace, Development and Communication, 2021)
This study is an attempt to find out the willingness of the journalists for self-censorship, to highlight the factors which give rise to the phenomenon of self-censorship and to investigate the impact of self-censorship on the journalists’ performance in Pakistan. This research has been conducted in the light of Bar-Tal model for self-censorship and it is quantitative based research. Questionnaire was distributed among 125 Islamabad-based journalists sampled through the purposive sampling method. Findings revealed that the majority of the journalists were facing self-censorship in Pakistan and they were not able to reveal the information in media without engaging in self-censorship. Researcher investigated the four factors which give rise to the phenomenon of self-censorship among the journalists in Pakistan; military, judiciary, media organization policies or media owner’s pressure and job insecurity. Researcher concluded that self-censorship affects the journalists’ performance, credibility, neutrality, free journalism, factual and objective reporting in Pakistan and self-censorship has negative impact on the journalists’ performance in Pakistan